Distribution of metals in suspended matter and bottom sediments in the estuary of the Northern Dwina. - Kukina, Natalia A; Sadovnikova, L K; Kalafat, A; Hummel, H; Regoli, Francesco (PANGAEA, 2002)
In 1995-1997 three oceanographic cruises to the White Sea were undertaken in the framework of the INTAS project 94-391, and a multi-disciplinary geochemical study of the major North Dvina estuary has been carried out. Distribution of temperature, salinity and concentration of suspended matter in water columm, as well as contents of Al, Fe, Mn, Co, Cu, Ni, Cr, Pb, Zn, and organic carbon contents in suspended matter and sediments of the North Dvina estuary were determined. Most of the metals and organic matter studied appear to be of terrestrial origin, since the main source of investigated elements in the estuary is river run-off. It was found that metals incorporated in minerals are absolutely prevailing forms in estuarine sediments, they comprise up to 60-99% of total metal contents. Two zones of metal accumulation in the sediments were found in the North Dvina estuary. These zones are considered as local geochemical barriers within a major river-sea barrier. Distribution of most elements studied in the sediments of the North Dvina estuary is controlled by grain size variability in the sediments. Analysis of data on heavy metal contents in the sediments and bivalves of the North Dvina estuary did not reveal any anthropogenic heavy metal pollution in the region.
Metals in suspended matter and bottom sediments from of North Dvina estuary
Keywords: Archive of Ocean Data; ARCOD; Dvinsk Gulf, White Sea; MULT; PVK95-D1; PVK95-D2; PVK95-D3; PVK95-D4; PVK95-D5; PVK96-1; PVK96-10; PVK96-11; PVK96-2; PVK96-3; PVK96-4; PVK96-5; PVK96-6; PVK96-7; PVK96-8; PVK96-9